Trends in Development and Determinants of Cross-Border Mergers and Acquisitions in the European Area - Gavurova , Beata; Gombar, Miroslav; Kascakova, Dagmara Ratnayake; Heckova, Jaroslava; Chapcakova, Alexandra (Transformations In Business & Economics, 2025)
Cross-border mergers and acquisitions (M&As) represent an important phenomenon of globalisation affecting the competitiveness of entire states (regions) and redistributing economic forces in the world. The driving forces underlying the trend to cross-border M&As are complex and vary by sector. The aim of the paper is to identify the impact of economic integration processes and the functioning of the European Monetary Union on the development of the volume and number of cross-border mergers and acquisitions in the countries of the European area. In the paper, based on the theoretical considerations of selected scientific studies, we analyse the influence of our selected predictors on cross-border mergers and acquisitions carried out in 19 source and 28 target countries of the European area and in Turkey in the period from 1998 to 2021 by modelling using structural equations. Our study provides a comprehensive overview of the trends and drivers of this surge in M&A activity in the EU, contributes to its better understanding and is complementary to already conducted research.
Keywords: European Union; European Monetary Union; cross-border mergers; cross-border acquisitions; sustainability; structural equation modelling